Az online személyiségi jogsértések a bírói gyakorlatban - Pádár, Henrietta (Debreceni Jogi Műhely, 2015)
This essay examines the judicial practice of infringements of personality rights in the online media. The purpose is to evaluate the effectiveness of the protection of legal regulation.The new media law that came into force in 2011 does not include specific measure for online media products, so it is up to the judicial practice to find a solution to tackle the problems brought forth by the differences of online and print press.Being a legal area where the legal development activity of the judicial practice plays a significant role due to the broad framework of regulation, the joint interpretation of legislation and the practice is necessary to evaluate. Thus the evaluation of the effectiveness of the protection of personality rights is only possible with the joint examination of legal environment and judicial practice.The starting point is the observation of the characteristics of online media and the comparison with print media through elements that can be relevant in a lawsuit.The investigation of the judicial practice focuses on the infringement of personality law and the process of press correction, considering that these are the most frequently occurring legal actions in lawsuits.